Transient thermal fatigue crack propagation behavior of a nickel-based single-crystal superalloy. (February 2020) - Pei, Haiqing; Wen, Zhixun; Wang, Zhaohan; Gan, Wenyan; Lu, Guang Xian; Yue, Zhufeng
Highlights: Transient thermal fatigue crack propagation behaviors of a Ni-based SX were studied. K and J -integral were calculated based on 3D transient thermo-mechanical theory. Anisotropic transient thermal fatigue crack model was developed. The effective crack ultimate length influence coefficient k eff was introduced. Three surface heat transfer stages were considered during water cooling process. Abstract: Thermal fatigue crack propagation behaviors of a V-notched Ni-based single-crystal superalloy DD6 were tested at 25 °C ↔ 760 °C/900 °C/1000 °C. The propagation directions of the two main cracks were approximately 45° with the dendrite orientation, and the {1 1 1} 〈1 1 0〉 slip family was mainly activated. Based on 3D transient thermo-mechanical coupling theory and rate-dependent crystal plasticity theory, the stress intensity factor and J -integral were calculated to predict the thermal fatigue crack propagation behavior. Three surface heat transfer stages were considered. The predicted crack propagation rates at three heating temperatures all showed good agreement with those obtained in the experiments.